Hint: Simplify everything first using .
Hello, I have these two equations but are really stumped as to how to solve them.
ln2 + ln(x+3) = 3
log3 + log(2x-1) = log2 + log(x+1)
I know the concept of multiplying when you have addition, and division when subtracting. In these two cases, I think I would be multiplying the terms as they are added ?
Can someone please get me started on these so I can see how to go about it.
Thanks kindly for any help.
not sure if I am on the right track, but I have factored the two to:
ORIGINAL: log3 + log(2x-1) = log2 + log(x+1)
FACTORED: log3(2x-1) = log2(x+1)
ORIGINAL: ln2 + ln(x+3) = 3
FACTORED: ln2(x+3) = 3
am I correct ?
If so, what is the next step ?
Thanks kindly for any help.